Effect of Learning Interest on Students' Study Habits at Accounting Department - Sibarani, Blasius Erik; Wulandari, Siska (Fakultas Ekonomi, Universitas Negeri Semarang, 2021)
The purpose of this study was to determine the effect of student interest in learning on the study habits of Accounting Department’s student. The population in this study were all 107 students of class X Accounting Department at State Vocational High School 2 Balige. The data collection technique was in the form of a questionnaire. This research was conducted by using descriptive and verification or causality. The data obtained were analyzed by using the PLS Algorithm test, PLS Bootstrapping and hypothesis testing using the t-test. The results of the analysis obtained that the average reflected variance was above 0.5 and the outer loading indicator was higher than 0.6. The hypothesis testing value seen from the p-value (0.007 0.05), meant that H0 was rejected, so learning interest had influence on study habits, and and also encouraged an increase in student learning outcomes obtained from good study habits. Suggestion is that students can increase their self-awareness and will be able to further foster enthusiasm on learning interest.